Salonica Fire of 1890 and its Impacts on the Transformation of the City - Özer Özbozdağlı (Belleten)

(untitled)
This study aims to evaluate the 1890 Salonica fire and its effects on the development of the city. Fires caused by natural causes or human error were part of everyday life in Salonica. Small fires were common for everyday life. But when fires grew, the consequences became devastating. The narrow and dead-end streets most affected by the fires were the Jewish quarters in the city center, where wooden houses were located. The existing wooden building stock of these neighbourhoods was the most important cause of the fires. These neighborhoods, with their old and wooden buildings, did not match the new modern face of the city. These neighborhoods had to be transformed according to the new urbanism and the zoning law of 1882. However, due to the current property situation of the region and the high cost of expropriation, the Municipality of Salonica could not enter these areas. At this point, the fire of 1890 was a turning point for the city. The fire caused a major humanitarian disaster, leaving thousands of people homeless. But the fire was an opportunity for the transformation of Salonica. The fire destroyed some of the Jewish neighborhoods with wooden buildings in the city center. The Municipality of Salonica, using the authority given by the zoning law of 1882, prohibited reconstruction in the area and prepared maps of the area. The burned areas were rebuilt according to the understanding of modern urbanism. This transformation marked the final phase of Salonica’s modernization.